2009
DOI: 10.3895/s1982-873x2009000200001
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de Representações Sociais sobre Física Quântica.

Abstract: ResumoEste trabalho apresenta resultados preliminares de uma investigação sobre possíveis representações sociais compartilhadas por diferentes grupos sociais, como estudantes do Ensino Médio, por exemplo. O objetivo é, utilizando análise multidimensional, identificar e caracterizar possíveis representações sociais a partir dos dados obtidos com o uso de testes de associação escrita e numérica de conceitos (TAEC e TANC). A compreensão dessas representações pode auxiliar no processo de aprendizagem significativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
1
4
0
2
Order By: Relevance
“…The three grades (1 st , 2 nd , and 3 rd ) had very similar configurations for the NWAT, as figures 1 and 2 show, and it is possible to notice the existence of two sets of words: terms associated to physics, in general -in the left -and terms associated to everyday life -in the right. Similar results were also obtained and discussed by Moreira et al (2009) and Hilger (2009) for configurations found for other research groups, also discussed these findings. On the other hand, configurations from WWAT related to high school students, can be found in Hilger et al (2009).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The three grades (1 st , 2 nd , and 3 rd ) had very similar configurations for the NWAT, as figures 1 and 2 show, and it is possible to notice the existence of two sets of words: terms associated to physics, in general -in the left -and terms associated to everyday life -in the right. Similar results were also obtained and discussed by Moreira et al (2009) and Hilger (2009) for configurations found for other research groups, also discussed these findings. On the other hand, configurations from WWAT related to high school students, can be found in Hilger et al (2009).…”
Section: Resultssupporting
confidence: 90%
“…The category we have considered the most relevant for this research on social representations is the one that deals with associations with words that appeared in texts, books, journals/magazines on quantum physics, such as thought, water, attraction, mind, brain, feelings, dimension, vibration, and so on. Oddly, the term "water" stands at the nucleus of representations of 1st and 2 nd year students (Hilger, 2009), and it is also related to quantum physics in the movie What the bleep do we know? 2 (Rocha, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations